Fish digestive lipase quantification methods used in aquaculture studies - Nolasco-Soria, Héctor (Frontiers in Aquaculture, 2023)
The proportion of fats or oils in natural or artificial feed is generally 6%–30%, since this is essential to cover fish’s energetic and structural requirements. Therefore, studies of the ontogeny or response of lipase activity to food treatments are widespread. A systematic review of articles published over 5 years (2016–2020) on lipase activity in fish in aquaculture was carried out; however, this was taken only as a representative example. Any 5-year period between 201-2022 would have shown similar results in terms of the actual lipase method used. As a result of this review, it was found that the methods used by the authors are very varied and have significant differences in terms of the type of substrate, substrate concentration, bile salt type and concentration, pH, temperature, incubation time, measurement of hydrolysis products, and definition of lipase units. The above does not mean that comparison of these studies is of no value, but that it is significantly limited. The most used methods (with p-nitrophenyl derivates, β-naphthyl derivates, and emulsified natural oils as substrate) can be reviewed to determine the most appropriate standard curves or the corresponding molar extinction coefficient for defining the lipase units. Standardizing current lipase analytical procedures should improve the reliability of comparative studies of aquaculture fish species.